What’s New in the Middle East? Classification of Muslim Scholars as Postcolonial Mufassirs - Muhammad Yusuf Pratama; Saffana Zahro Dinayah; Dewi Fatimatul Khoiriyah; Siti Fatimah Azzahro; Agus Imam Kharomen (UIN Imam Bonjol Padang, 2025)
The postcolonial Middle East faces complex dynamics between colonial legacies, religious identity and the demands of modernity. The development of Qur’ānic interpretation by contemporary Muslim scholars is a critical response to the hegemony of colonial thought as well as an attempt to reconstruct the meaning of religion in a new socio-political context. The tension between the authenticity of tradition and the need to reinterpret the text marks the intellectual struggle in this area. This article analyzes the contribution of postcolonial Muslim thinkers in transforming tafsir discourse. It also explores the influence of their thought on the development of Islam in the Middle East. This is a qualitative research using a descriptive-interpretative analytical approach to primary and secondary data (study of related literature). Through this research, it can be seen that postcolonial Muslim scholars are divided into three groups, from those who maintain classical theories to those who introduce contextual-historical approaches in tafsir, integrating social criticism, hermeneutics, and epistemological decolonization. Their thinking encourages a religious dialectic that is more inclusive and responsive to global issues. This research contributes to enriching the discussion of contemporary Islamic studies by highlighting the interaction between postcolonialism and Muslim intellectual transformation